2013
DOI: 10.1016/j.febslet.2013.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase subtilisin/kexin type 9 potentially influences cholesterol uptake in macrophages and reverse cholesterol transport

Abstract: Edited by Laszlo NagyKeywords: PCSK9 Reverse cholesterol transport Low-density lipoprotein receptor Atherosclerosis a b s t r a c t Proprotein convertase subtilisin/kexin type 9 (PCSK9) promotes the degradation of low-density lipoprotein receptor (LDLRs) molecules expressed on the cell surface. Gene inactivation of PCSK9 reduces the areas of atherosclerotic lesions in mice, and the effect is mainly dependent on LDLRs. Furthermore, a positive relationship between PCSK9 and cholesterol accumulation in the wall o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Previously, Ferri et al ( 77 ) reported that PCSK9 is expressed in human vessel walls and produced locally by vessel smooth muscle cells causing a local effect, and it was suggested that PCSK9 could enter the subendothelial space from the circulation either by itself or in association with LDL. In addition, it has been hypothesized that PCSK9 could impact the expression of LDLR on lesion monocytes and macrophages modulating foam cell formation and/or promoting apoptosis ( 78 ). Although our analysis was quite limited, we conclude that PCSK9-mediated local effects at the lesion, refl ected by lesion area and macrophage number, is not signifi cant in the models utilized here.…”
Section: Discussionmentioning
confidence: 57%
“…Previously, Ferri et al ( 77 ) reported that PCSK9 is expressed in human vessel walls and produced locally by vessel smooth muscle cells causing a local effect, and it was suggested that PCSK9 could enter the subendothelial space from the circulation either by itself or in association with LDL. In addition, it has been hypothesized that PCSK9 could impact the expression of LDLR on lesion monocytes and macrophages modulating foam cell formation and/or promoting apoptosis ( 78 ). Although our analysis was quite limited, we conclude that PCSK9-mediated local effects at the lesion, refl ected by lesion area and macrophage number, is not signifi cant in the models utilized here.…”
Section: Discussionmentioning
confidence: 57%
“…It is possible that in apheresis patients the acute elimination of the PCSK9 protein may also improve the effectiveness of lipid-lowering drugs. It has been suggested that PCSK9 may be directly involved with the formation of atherosclerotic lesions by increasing oxidized LDL uptake and impairing macrophage-mediated reverse cholesterol transport [28]. Additionally, hypertensive patients with elevated serum PCSK9 levels were associated with increased carotid intima media thickness [29].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Shen et al . suggested that PCSK9 contributed to subendothelial oxidized LDL accumulation, which in turn might reduce SR‐B1 expression 22.…”
Section: Pcsk9 and Lipoprotein Receptorsmentioning
confidence: 99%